1983
DOI: 10.1111/j.1095-8649.1983.tb02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐ stocking movements and recapture of hatchery‐reared trout released into flowing waters—effect of prior acclimation to flow

Abstract: Hatchery-reared brown trout, Salmo truttu, (F.L., 16-27 cm) were stocked into the Afon Clettwr, Afon Western Cleddau and Afon Dysynni, Wales. The effects of (a) retaining fish caged in the river for 24 h before release, and (b) a period of acclimation to flowing water (up to 0.24 m S-I) in tanks prior to stocking were investigated. Data on percentage recapture and post-stocking movements were obtained from trapping, electrofishing and tag returns. In-stream acclimation resulted in a higher percentage recaptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 6 publications
5
39
1
Order By: Relevance
“…1999). Similarly, holding brown trout in enclosures for 24 h at the site of release had a positive effect on the number of fish recaptured (Cresswell and Williams 1983).…”
Section: Management Techniquesmentioning
confidence: 99%
“…1999). Similarly, holding brown trout in enclosures for 24 h at the site of release had a positive effect on the number of fish recaptured (Cresswell and Williams 1983).…”
Section: Management Techniquesmentioning
confidence: 99%
“…In‐stream acclimatization before release can reduce this stress through adaptation to water currents, natural food, etc. and increasing the period of acclimatization decreases stress and post‐stocking downstream movements in fluvial Arctic grayling (Kaya & Jeanes 1995) and brown trout (Cresswell & Williams 1983; Jonsson, Brännäs & Lundqvist 1999). Whether this also applies to European grayling is not known.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably a result of the acclimatisation period the fish go through before being released into the wild habitat. Investigators have observed increases in survival with short acclimation periods (<7 days) for stocked fish (Cresswell and Williams, 1983;Jonssonn et al, 1999;Brennan et al, 2006). Fish released from grow-out pens in this study where held for an average of 160 days (range 14-837 days).…”
Section: Discussionmentioning
confidence: 96%